Determination of neutron energy spectrum at KAMINI shielding experiment location. (September 2016) - Sen, Sujoy; Bagchi, Subhrojit; Prasad, R.R.; Venkatasubramanian, D.; Mohanakrishnan, P.; Keshavamurty, R.S.; Haridas, Adish; Arul, A. John; Puthiyavinayagam, P.
Abstract: The neutron spectrum at KAMINI reactor south beam tube end has been determined using multifoil activation method. This beam tube is being used for characterizing neutron attenuation of novel shield materials. Starting from a computed guess spectrum, the spectrum adjustment/unfolding procedure makes use of minimization of a modified constraint function representing (a) least squared deviations between the measured and calculated reaction rates, (b) a measure of sharp fluctuations in the adjusted spectrum and (c) the square of the deviation of adjusted spectrum from the guess spectrum. The adjusted/unfolded spectrum predicts the reaction rates accurately. The results of this new procedure are compared with those of widely used SAND-II code. Highlights: Determination of neutron energy distribution using foil activation measurements: Spectrum Unfolding. Iterative perturbation and least squared method. Monte Carlo technique for neutronic calculation. Gamma spectroscopy for activation calculation. Estimation of self shielding correction factors in foil activation.